Comparison of the effectiveness of low-energy laser treatment and sonotherapy in the healing of plantar aponeurosis enthesopathy symptoms - Bloch, Agata; Misiak, Kinga; Nowicki, Łukasz; Złotnik, Anna; Kałużny, Krystian; Kałużna, Anna; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The aim of this study is to compare the effectiveness of healing using low-energy laser treatment and sonotherapy in the treatment of plantar aponeurosis enthesopathy symptoms. Material and methods: The research was carried out at the hospital in Lipno. The research group consisted of 50 people with diagnosed enthesopathy of the plantar aponeurosis and mostly with an excessive BMI index. The patients were divided into two groups. The first one consisted of 25 patients who were treated with low-energy laser therapy. The second group with the same number of people was treated by sonotherapy. A research group of 50 people suffering from plantar aponeurosis and mostly with an excessive BMI (D = 26.9). Women: 33 and men: 17 at the age from 36 to 73 (D = 59.7). Results: The results obtained in the VAS scale show that low-energy laser treatment and sonotherapy, as the form of ultrasounds, are effective pain treatments of the plantar aponeurosiys enthesopath. Both treatments reduce the subjective feeling of pain. Also, the intensity of pain associated with enthesopathy decreases when using low-energy laser therapy. Both treatments significantly affect the reduction of edema around the plantar aponeurosis. Sonotherapy reduces pain but does not significantly affect the frequency of pain. Both therapies proved to be effective, but the studies showed statistically significant differences between the studied groups. The improvement with a greater severity was noted in group II, treated by sonotherapy, as the form of ultrasounds. Conclusions: The results obtained in the tests showed a therapeutic effect in reducing pain associated with plantar aponeurosis, nonetheless the comparison of both physical methods showed a statistically significant difference between the groups studied. The improvement with a greater severity was noted in group II, treated by sonotherapy, as the form of ultrasounds.